PENERAPAN ACTIO PAULIANA TERHADAP PERLINDUNGAN KREDITUR DALAM PROSES KEPAILITAN - Martin Ezra (2022)
Actio pauliana is an attempt by the Curator to cancel the acts committed by the bankrupt debtor. In this case, what was studied was actio pauliana which was implemented in Decision Number 20/Pdt.Sus-Lat on Others AP/2019/PN.Niaga.Jkt.Pst. jo. Number 119/Pdt.Sus-PKPU/2018/PN.Niaga.Jkt.Pst. (PT. Jabatex), apart from that, the legal consequences of the cancellation of the transfer of bankrupt assets by the debtor were also examined. This study aims to explain the application of actio pauliana by the curator in the case study of PT. Jabatex. The research method used in this paper is a normative research method, using the actio pauliana case approach of PT. Jabatex. The analysis of this problem is how actio pauliana can be pursued by the curator in the event of an act in bad faith committed by a bankrupt debtor and the next problem is what are the legal consequences for canceling the transfer of bankrupt assets by the debtor who, that his actions were against the law, does not have moral and does not provide justice for creditors and curators. The suggestion in this study is that the government should make a list of records for naughty debtors, to protect the interests of the general public as well as additional sanctions due to the actions of naughty debtors.